1996
DOI: 10.1063/1.471672
|View full text |Cite
|
Sign up to set email alerts
|

Molecular photoionization as a probe of vibrational–rotational–electronic correlations

Abstract: We determine the rotationally state-resolved 2σu−1 photoionization of N2 into alternative vibrational channels as a function of energy over a 200 eV range. Experiment and theory reveal that Cooper minima highlight the coupling between electronic, vibrational, and rotational degrees of freedom over this very wide range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…[30][31][32][33][34][35] In particular, we showed that rotational distributions in N 2 photoionization were strongly influenced by Cooper minima in the lϭ2 partial wave of the 2 u →k g channel over a 250 eV range. [32][33][34][35] An interesting and unexpected result of those previous studies was that the rotationally resolved characteristics of N 2 2 u Ϫ1 and CO 4 Ϫ1 photoionization were qualitatively different for these valence isoelectronic systems. The differences were attributed to qualitative differences in their ionization continua.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34][35] In particular, we showed that rotational distributions in N 2 photoionization were strongly influenced by Cooper minima in the lϭ2 partial wave of the 2 u →k g channel over a 250 eV range. [32][33][34][35] An interesting and unexpected result of those previous studies was that the rotationally resolved characteristics of N 2 2 u Ϫ1 and CO 4 Ϫ1 photoionization were qualitatively different for these valence isoelectronic systems. The differences were attributed to qualitative differences in their ionization continua.…”
Section: Introductionmentioning
confidence: 99%
“…The high energy behavior results from the strong dependence of the Cooper minima on bond length. 5,6 The low energy region is featureless because there is no shape resonance corresponding to the one observed in CO. This stems from symmetry, i.e., the lϭ3 partial wave is forbidden in the case of N 2 because the final electronic wave function is of gerade symmetry and therefore contains only even partial waves.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3]5 The excursion in the CO vibrational branching ratio curve at h Ϸ35 eV results from the lϭ3 shape resonance in the 4 →k channel. 2,4 The higher energy regime is featureless because there is no shape resonance at higher energies, and the Cooper minima are relatively weak.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations